Getting students to read for pleasure through the sustained silent reading program in the school library - Gapuz, Micaela Virginia P.; Cabbab, Johann Frederick A. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
The researcher believes that the Sustained Silent Reading (SSR) program is as practical way to encourage students to read for pleasure. It is a reading program which regularly allots a certain period of time to students to read anything that is of interest to them. However, since most of the SSR programs in previous researches were conducted in the classroom rather than the library, the researcher experimented with the SSR in library to find out if it was a more effective venue for the said reading program for improving students' attitude towards reading and their library use rather than the classroom. To be able to answer this, the researcher divided the Cornerstone Christian Academy of Quezon City high school students into three groups-Experimental group 1 (those who used their library as the venue for SSR); Experimental group 2 (those who used their classroom as the venue for SSR); and the Control group (those who did not participate in any program).
Results have shown that there was an increase in the reading attitude of all groups. However, only the mean score of Experimental group 1 during the pretest and posttest had a statistically significant difference having a p-value of 0.02 which is less than 0.05. For the student library use, pretest scores were higher than the posttest score in the students' library visit and in the number of books they borrowed of all the groups except for the Control group which had an increase of 1 in the number of books borrowed.
For the library visits, Experimental group 1's pretest result total was 65 and it dropped to 33 in the posttest. Experimental group 2's pretest results total was 59 and also dropped to 43 in the posttest. As for the Control group, their pretest result total for their library visits was 49 and their posttest result total was 35. For the number of books borrowed by the students, Experimental group 1's pretest result total was 8 and was halved during the posttest with 4. Experimental group 2's pretest total was 6 and dropped to 2 during the posttest. For the Control group it had a pretest result total of 9 and a posttest result total of 10. Even though it had an increase of 1, statistics showed that there is still no significant difference in their pretest and posttest results.
The program also helped increase the number of students who said they liked reading for 65 to 78. There were also positive effects in the students' reasons why they use their library and the materials they read. Before the SSR was implemented, the top 2 reasons why the students go to their library were to do research (45) and because it was necessary (45). After the program the top two reasons were to do research (53) and to read (39). As for the reading materials, before the SSR was implemented, the top two materials that the student read were magazines 69 and comics (69). After the program was implemented, the top two materials that the students read were Fiction books (71) and Comics (69). The researcher recommends that the SSR be conducted in the library once or twice a week for longer periods rather than for 10 minutes everyday.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: School libraries -- Activity programs; Literacy programs; Silent reading